2010
DOI: 10.2174/1876396001003010006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Honey and Its Role in Preventing Health Disorder

Abstract: Honey is being used since long time both in medical and domestic needs, but only recently its antioxidant property has come to limelight. With increasing demand for antioxidant supply in the food, honey is becoming popular as a source of antioxidant since it is rich in phenolic acids and flavonoids and other antioxidants including glucose oxidase, catalase, ascorbic acid, carotenoid derivatives, organic acids, amino acids and proteins. The antioxidants have several preventative effects against different diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 42 publications
1
63
1
Order By: Relevance
“…Honey feeding to animals suppressed cisplatin‐induced inflammation in the kidney which includes leukocyte infiltration, cytokine and chemokine production and cytokine excretion in urine. Honey is known to have phenolic compounds that may be responsible for the observed effects on inflammation. NFkB activation by cisplatin is a major mediator of inflammatory response in the kidney in response to cisplatin administration .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Honey feeding to animals suppressed cisplatin‐induced inflammation in the kidney which includes leukocyte infiltration, cytokine and chemokine production and cytokine excretion in urine. Honey is known to have phenolic compounds that may be responsible for the observed effects on inflammation. NFkB activation by cisplatin is a major mediator of inflammatory response in the kidney in response to cisplatin administration .…”
Section: Discussionmentioning
confidence: 99%
“…It's a highly saturated solution consisting of fructose (38%) and glucose (31%) as the major constituents, whereas the rest of the solution's composition is constituted by minor constituents such as phenolic acids, flavonoids, ascorbic acid, certain antioxidant enzymes such as glucose oxidase and catalase, carotenoid‐like substances, organic acids and Maillard reaction products . These minor constituents are reported to be mainly responsible for the antioxidant properties of honey . To date, many epidemiological studies have demonstrated the effectiveness of phenolics and flavonoids when used alone or in combination as antitumor or anti‐inflammatory agents, in the treatment of cataracts or in reducing the risk of cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imbalance between oxidative stress and antioxidant scavengers leads to damage of important biomolecules resulting in malonaldehyde (MDA) production 45 and the body has a defense mechanism against its harmful effects through neutralizing the free radicals by means of either endogenous enzymatic glutathione peroxidase (GPX) and superoxide dismutase (SOD) 46 or non-enzymatic e.g. catalase, alkaloids, ascorbate, 47 flavonoids 8,48 selenium, 46 vit C and vit E. 49 Honey antioxidant activity exhibited by different bioactive micro components 50 such as flavonoids, 8,9 phenolic compounds, 51 chrysin 52 and amino acids 53 but the main antioxidants are considered to be the polyphenols. 54 Different antinociceptive effects of different fractions from Chinese EEP mainly chrysin, 55 but honey 6 or propolis 55 chrysin as a polyphenolic compound or galanin 56 -which is an abundant component in honey -has anti-inflammatory 3 and antioxidant properties 57 enhancing protein stability, 52,58 solid lipid nanoparticle (SLN) synthesis avoiding proteolytic degradation 52 resulting antiploliferating 6,59 action.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…These medicinal properties of honeys are proposed to be derived from phytochemicals especially flavonoids present in them which are found to be varying in proportions with respect to the geographical area, climate and flora of origin 11 . Some of the polyphenols of honey have been evolved as promising pharmacological agents in treatment of cancer 12 . Hamzaoglu et al reported that tumour implantation in rats was markedly reduced by the application of honey pre-and postoperatively, suggesting that the physico-chemical action, decrease of oxygen availability in the tumour environment, i.e., anti-angiogenic effect prevented the spread of metastatic cells 13 .…”
Section: Introductionmentioning
confidence: 99%